2016
DOI: 10.1186/s12931-016-0355-2
|View full text |Cite
|
Sign up to set email alerts
|

Expression of toll-like receptors 2 and 4 in subjects with asthma by total serum IgE level

Abstract: BackgroundEmerging data suggest that innate immunity may play a role in asthma, particularly the toll-like receptors (TLRs). Some studies pointed to an involvement of TLRs 2 and 4 in the pathogenesis of allergic asthma, and other studies related TLRs to IgE. However, there are not any studies that have comprehensively evaluated the expression of TLRs 2 and 4 in inflammatory cells, in peripheral blood and induced sputum specimens from asthmatic patients, according to their total serum IgE.MethodsWe studied 44 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 45 publications
0
8
0
1
Order By: Relevance
“…The serum total IgE might play a role as a mediator in the development of allergic diseases. The high serum total IgE concentration was associated with the risk for allergic sensitization [33], In addition, high serum total IgE increased macrophage expression of TLR4 in induced sputum in asthmatic subjects [34]. This outcome may result from a link between innate immunity and IgE-mediated adaptive immune responses in asthma.…”
Section: Discussionmentioning
confidence: 99%
“…The serum total IgE might play a role as a mediator in the development of allergic diseases. The high serum total IgE concentration was associated with the risk for allergic sensitization [33], In addition, high serum total IgE increased macrophage expression of TLR4 in induced sputum in asthmatic subjects [34]. This outcome may result from a link between innate immunity and IgE-mediated adaptive immune responses in asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Asthma is a chronic disorder of the airways associated with episodes of bronchial constriction, mucus production, and immune cell infiltration. The inflammation associated with disease can be driven by allergic or non‐allergic mechanisms, where the activation of Toll‐like receptors (TLRs) on epithelial cells and macrophages regulates the initial nature of the innate inflammatory response . TLR4 activation in response to bacterial components, such as lipopolysaccharide (LPS), will drive nuclear factor (NF)‐κB‐driven inflammatory programming towards IL‐1β, IL‐6, and TNF‐α production in macrophages, promoting the activity of type 1 (M1)‐resident populations and neutrophilic inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…These studies demonstrated that TLR4 function is likely to be required also in the airway epithelia, which might undermine the barrier function of the epithelium ( 27 , 34 ). Nevertheless, asthmatic subjects with high total serum IgE show increased macrophage expression of TLR4 in induced sputum ( 35 ). Thus, the aim of this study was to investigate the role of TLR4 in asthma-like features such as inflammatory infiltrate, airway hyperreactivity, and mucus exacerbation in mice exposed to S1P.…”
Section: Introductionmentioning
confidence: 99%